Senegal : Do Hygiene and Handwashing Make for Better Brain Development? - World Bank (Washington, DC, 2017)
Poor hygiene is a particular problem when it comes to children because they are more susceptible to diarrhea and repeated or severe episodes can harm their health and development. Every year, 800,000 children under the age five die from diarrheal disease. Recurrent episodes of diarrhea can also hurt a child’s ability to absorb nutrients and this can contribute to health problems and physical and mental stunting. As a result, many governments and organizations have created programs to encourage better hygiene practices and handwashing with soap during critical times, such as before eating and after using the toilet. These simple practices have been proven to substantially reduce the spread of illnesses. The Government of Senegal, working with the Water and Sanitation Program, launched a three-month national promotion campaign in 2009 that used mass media, including radio, television, and billboards, to encourage people to wash their hands with soap and water. In the campaign’s second phase, a more intensive, locally focused promotion campaign was rolled out in seven of the country’s 11 regions. This ten-month program relied on community events to inform people about handwashing and to influence their views and behavior to get them to use soap and water regularly.